Heart rate variability in individuals with cerebral palsy - Kerppers, Ivo I.; Arisawa, Emilia A.L.; Oliveira, Luis V.F.; Sampaio, Luciana M.M.; Oliveira, Claudia S. (Archives of Medical Science, 2009)
Introduction: Cerebral palsy (CP) is a non-progressive brain pathology that mainly affects the motor system. Heart rate variability is currently used as an assessment tool for the balance in the sympathetic and parasympathetic branches of the autonomic nervous system (ANS). The aim of the present study was to determine abnormalities in the ANS in patients with cerebral palsy submitted to the Slump Test for analysis of heart rate variability. Material and methods: The sample was made up of 18 individuals with cerebral palsy, aged 8 to 27 years. For data collection, the Nerve-Express software program was used, performing the orthostatic test on all individuals in the sample. The Slump Test was administered 3 times, with 3-min intervals between tests, collecting data each time. Results: Average age was 18.7 years; average BMI was 16.0 kg/m 2 . The Gross Motor Function Classification System demonstrated predominance in the sample of individuals with level V diparesis. Analysis of the data revealed a decrease in parasympathetic activity and an increase in sympathetic activity. Analyzing the characterization of the sample to the levels of functioning of the physiological systems and adaptation reserve revealed a decrease of these functions after the test, although it was not significant. Conclusions: The results from the experimental conditions employed allow the conclusion that the individuals with cerebral palsy in the present sample demonstrated no statistically significant difference between SNS and PNS activity. However, after applying the Slump Test an improvement was noted in the chronotropic myocardial reaction, functioning of the physiological systems and adaptation reserve.